Commodity Market Risk as a Determinant of Corporate Capital Structure - Konrad SZYDŁOWSKI (Communications of International Proceedings, 2024)
The article addresses the problem of managing the capital structure of enterprises in the conditions of  commodity market risk. The problem of capital structure determinants is well documented, but the impact of oil price volatility still remains a research gap. The article also sheds new light on the problem of capital structure management in a turbulently changing economic environment. The research goal was to determine the importance of the volatility of crude oil prices as a determinant of capital structure. The analysis was based on the group of companies which represent the oil industry. Research showed that the volatility of oil prices is an important determinant of the financial condition of companies. This particularly applies to the capital structure. The decrease in oil prices resulted in a decline in profitability and financial liquidity. This proves the deterioration of the financial condition of the analyzed companies. Simultaneously, an increase in debt was observed. The opposite effect was identified during periods of growth. These trends were particularly clear in subperiods of dynamic trends in oil market.
Keywords: price risk; commodity market; capital structure.